G232(P) Follow up of children with minor renal scarring. (May 2019) - Kaviethasan, S; Morgan, H; Hesseling, M
Abstract : Introduction: According to NICE guideline CG54, infants and children with a minor, unilateral renal parenchymal defect do not need long term follow up unless they have recurrent UTI or family history or lifestyle risk factors for hypertension. Minor scarring is defined as unilateral renal parenchymal defect with divided function within normal limits. In our experience these children are still being followed up in many hospitals. Aim: We conducted a study looking at how many children are followed up contrary to NICE guideline CG54 and to identify high blood pressure in children with minor renal scarring. Methods: Retrospective analysis of Dimercaptosuccinic acid (DMSA) scan results from July 2007 to June 2016 was done at a tertiary centre in 2017 and then at a district general hospital (DGH) for the period of January 1997 to September 2017. Results: Tertiary centre: amongst a total of 8220 DMSA scans, 174 scans were identified to have only minor renal scarring and 65 patients were followed up with a median follow up duration of 2.29 years (range 1month- 9 years). In 45% (29/65) blood pressures were recorded in clinic all of which were within normal limits. Among those under ongoing follow up 95% (38/40) had other clinical issues and 5% (2/40) were followed up for minor renal scarring only. DGH: Amongst a total of 962 scans, 27 were identified to have only minor renal scarring and 23 patients were followed up locally. Median follow up duration was 5 years (range 5 month-17 years). 96% (22/23) had blood pressures recorded. One patient was found to have minor renal scarring when investigated for high blood pressure. 74% (17/23) discharged from follow up while 26% (6/23) had ongoing follow up. All of them (6/6) were followed up for minor renal scarring only. 3out of these 6 however did not attend further follow up. Conclusion: Our study suggest that there are still children being followed up unnecessarily in contradiction to NICE Guideline CG54 both in tertiary centres and DGHs.